Planning for equity: an evaluation of hazard mitigation plans - Abell, Zachary Hayden (Kansas State University, 2023)
Natural hazards present a significant challenge to communities of all sizes. From a tornado in a small Midwestern town to a hurricane that floods an entire coastal city, their adverse effects can impact a community’s social and economic infrastructure for months or even years after the dust has settled or the water receded. Flooding is one of the most deadly and costly natural disasters we face as a society. Prior studies showed that some populations are more prone to experiencing damage from flooding purely based on socioeconomic factors. In this report, I address this disparity in risk exposure and explore the extent to which hazard mitigation plans address this equity issue; and how it varies by cities with different levels of flood hazard exposure. Using content analysis and plan quality metrics derived from an existing Equity Evaluation Tool, modified for the parameters of this research, I conducted an analysis of the planning documents that are used to guide hazard planning practices in cities around the United States. Seventeen cities were selected for their varying levels of flood exposure amongst vulnerable populations. After analyzing the documents with the modified Equity Evaluation Tool, “Equity Scores” were given to each hazard mitigation plan. It was found that Hazard Mitigation Plans for areas with higher levels of unequal flood exposure receive lower Equity Scores compared to other cities. This finding points to an alarming trend in Hazard Planning practices in riverine communities in the United States.
Keywords: Planning; Hazard mitigation; Equity